The Language of Praise and Worship: A Corpus Analysis of Register Variation in Christian Songs - Raymund T. Palayon; Irish Mae Dalona (Southeastern Philippines Journal of Research and Development, 2025)
Songs play a central role in Christianity, not only as musical expressions of faith but also as powerful tools for influencing beliefs and behavior. Some churches utilize hymns, while others prefer contemporary Christian songs. Despite their significance in shaping religious views and practices, the language of Christian songs remains underexamined in linguistic research. Previous studies have analyzed only a small number of texts and focused on limited linguistic features, providing a limited understanding of their stylistic functions. This paper examined the key linguistic features in the two sets of Christian songs—church hymns and contemporary Christian songs—to illustrate their register variation, using multidimensional analysis, key semantic tag analysis, and key part-of-speech analysis. From the analyses, the church hymns display features associated with scriptural texts (e.g., God, salvation, Jesus), adoration (e.g., glory, bless, rejoice), and appreciation (e.g., gracious, thankful, grateful), illustrating the informational and context-independent characteristics in these songs. The contemporary Christian songs display features associated with life-related situations (e.g., breakdown, failure, loss), spiritual relationships (e.g., me, you), and an engaging style of communication (e.g., I, we, your), illustrating the context-dependent and persuasive characteristics in these songs. This study provides a framework for characterizing the linguistic features of worship songs from non-Christian contexts, enabling future research to compare religious music across different traditions.
Keywords: Media, Communication, and Education; Historical and Linguistic Studies; Linguistic Variation and Morphology